Effect of CNFs-Ni/LDPE electrode on space charge injection in LDPE insulating layer. Issue 1 (1st August 2022) - Xing, Zhaoliang; Hu, Xiangnan; Liu, Yujia; Hao, Ming; Zhang, Chong; Hao, Chuncheng; Lei, Qingquan
Abstract: The accumulation of space charge is considered to be an important key factor to accelerate the aging of the insulation of HVDC cables. How to reduce the accumulation of space charge in the insulation layer is an urgent problem to improve the voltage level of cables. In this paper, an approach is presented to prevent charge from the inner semiconductive layer to the insulating layer, using a modified semiconductive compound by doping magnetic carbon nanofibers. Through microwave-assisted heating, Ni was deposited on the surface of carbon nanofibers which have been pre-treated. Modified semiconductive compound electrodes was used to test the injection of charges. The results showed that charge injected into LDPE insulting layerwith modified CNFs-Ni/ LDPE electrode is less than that with LDPE semiconductive layer without CNFs-Ni electrode.